Venetoclax plus low-intensity chemotherapy for adults with acute lymphoblastic leukemia - Marlise R. Luskin; Shai Shimony; Julia Keating; Eric S. Winer; Jacqueline S. Garcia; Richard M. Stone; Elias Jabbour; Yael Flamand; Kristen Stevenson; Jeremy Ryan; Zhihong Zeng; Anthony Letai; et al. (Blood Advances)
Abstract: In acute lymphoblastic leukemia (ALL), the B-cell lymphoma 2 inhibitor venetoclax may enhance the efficacy of chemotherapy, allowing dose reductions. This phase 1b study of venetoclax plus attenuated chemotherapy enrolled 19 patients with ALL either newly diagnosed (aged ≥60 years, n = 11 [B-cell, n = 8; T-cell, n = 3]) or relapsed/refractory (R/R; aged ≥18 years, n = 8 [B-cell, n = 3; T-cell, n = 5]). Venetoclax was given for 21 days with each cycle of mini–hyper-CVD (mini-HCVD; cyclophosphamide, vincristine, dexamethasone alternating with methotrexate and cytarabine). There were no dose-limiting toxicities at dose level 1 (DL1; n = 3, 400 mg/d) or DL2 (n = 6, 600 mg/d); DL2 was the recommended phase 2 dose and explored further (n = 10). The most common nonhematologic adverse events were grade ≥3 infections. There were no deaths within 60 days. There was no tumor lysis syndrome, hepatotoxicity, prolonged cytopenias, or early discontinuation for toxicity. Among patients with newly diagnosed ALL, 10 of 11 (90.9%) achieved a measurable residual disease–negative (<0.01% sensitivity) complete remission (CR) including 6 patients with hypodiploid TP53-mutated ALL. All patients in CR bridged to hematopoietic stem cell transplant (n = 9) or completed protocol (n = 1). With a median follow-up of 60 months, median disease-free survival (DFS) for patients with newly diagnosed ALL was 54.6 months (95% confidence interval [CI], 35.5 to not available), with a 2-year DFS rate of 90% (95% CI, 71-100). Among patients with R/R ALL, 3 of 8 (37.5%) achieved CR. In summary, for patients with newly diagnosed ALL, venetoclax plus mini-HCVD is well tolerated with promising efficacy. This trial was registered at www.clinicaltrials.gov as #NCT03319901.